Kontribusi Dayah Darul Ihsan dalam Pembinaan Pendidikan Keagamaan Masyarakat Darussalam Aceh Besar - Lismawani, Lismawani (Tadabbur: Jurnal Peradaban Islam, 2020)
Dayah is a place for studying religion for the community and also as a guide for the community in terms of religious education, so the dayah is needed to guide and direct the community so that all their behavior and behavior are in accordance with the teachings of Islam. This research is elaborated into several problem formulations as follows: (1)How is the partnership between Dayah Darul Ihsan and local communities in Siem, Aceh Besar (2) How does Dayah Darul Ihsan give religious education for the local communities of Aceh Besar (3) What are the supporting factors and obstacles faced by Darul Ihsan in the implementation of religious education programs for local communities of Aceh Besar. This study uses a type of qualitative descriptive research with methods of collecting data through interviews, observations and documents. As well as using interactive data analysis techniques with flow stages: data collection, data reduction, data presentation, and conclusions or verification.